2015
DOI: 10.1177/0886260515608802
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs of Palestinian Women From Israel About the Responsibility and Punishment of Violent Husbands and About Helping Battered Women

Abstract: This article presents a study that examined beliefs about violent husbands and about helping battered women among Palestinian women living in Israel from the perspective of patriarchal ideology. A convenience sample of 701 married women was obtained, and a self-report questionnaire was administered. The findings reveal that the majority of participants held violent husbands accountable for their behavior; however, the majority of them did not support punishing violent husbands through formal agencies (i.e., th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…This is consistent with findings on wife abuse in other Arab societies in which women had more positive attitudes toward wife abuse (Haj-Yahia, 2002b, 2005. Furthermore, the findings of this study are consistent with studies that showed a higher level of support for social work interventions among younger individuals in Arab societies (Haj-Yahia, 2002a;Haj-Yahia & Zaatut, 2015). This is also consistent with findings from several studies showing more positive and accepting views and attitudes toward wife abuse in Arab societies among women and younger individuals (Haj-Yahia, 2002b, 2005.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with findings on wife abuse in other Arab societies in which women had more positive attitudes toward wife abuse (Haj-Yahia, 2002b, 2005. Furthermore, the findings of this study are consistent with studies that showed a higher level of support for social work interventions among younger individuals in Arab societies (Haj-Yahia, 2002a;Haj-Yahia & Zaatut, 2015). This is also consistent with findings from several studies showing more positive and accepting views and attitudes toward wife abuse in Arab societies among women and younger individuals (Haj-Yahia, 2002b, 2005.…”
Section: Discussionsupporting
confidence: 92%
“…The study findings are consistent with studies showing the effect of having egalitarian versus traditional views about marital roles on various views and attitudes toward wife abuse in Arab and non-Arab patriarchal societies (Haj-Yahia, 2002a, 2003, 2005; Haj-Yahia & Shen, 2015; Haj-Yahia & Uysal, 2008). Studies have also shown that lower levels of support for helping battered women were associated with holding more traditional (nonegalitarian) views toward women and marriage among Palestinian women from Israel (Haj-Yahia & Zaatut, 2015) and among Arab immigrant women in the United States (Abu-Ras, 2007). This further emphasizes the influence of traditional and patriarchal views that seeking outside help for wife abuse is perceived as disruptive to the cohesiveness of the family, particularly as it is related to the collectivist and patriarchal nature of Arab society.…”
Section: Discussionmentioning
confidence: 99%
“…Arab societies are no exception; gender inequality exists in socioeconomic, law, and political spheres (Moghadam, 2004). In most Arab societies including Libya, the right of men to control and chastise women is accepted, justified, and legalized (Abu-Hilal & Aal-Hussain, 1997; Gharaibeh & Al-Ma’aitah, 2002; Haj-Yahia & Zaatut, 2015). Therefore, the husband is culturally the central authority, to whom the wife and children must ultimately respond (Barakat, 1993; Haj-Yahia, 2011; Haj-Yahia, Musleh, & Haj-Yahia, 2002; Joseph, 1993).…”
Section: Gender Regimes In Muslim/arab Communitiesmentioning
confidence: 99%
“…Evidence also suggests that women also tend to oppose punishment for IPV related aggressive behaviour (Haj-Yahia, 2002;Haj-Yahia & Zaatut, 2015;Horn, Puffer, Roesch, & Lehmann, 2016).…”
Section: Introductionmentioning
confidence: 99%